PENINDASAN TERHADAP PEREMPUAN DALAM NOVEL PEREMPUAN DI TITIK NOL DAN MIDAH SI MANIS BERGIGI EMAS: KAJIAN SASTRA BANDINGAN - Kristin Marwinda (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
The purpose of this study is to compare two kinds of literary work from two different countries about women oppression experienced by the main character in the novel. The objects analyzed in this study are Perempuan di Titik Nol by Nawal el-Saadawi, an author from Egypt, and Midah Si Manis Bergigi Emas by Pramoedya Anantha Toer from Indonesia. This comparative literature study uses the theory of feminism. The method of this study is descriptive qualitative based on the library research. The results of this study show that there are significant differences between women oppression experienced by the main characters, although both novels have same theme which is the struggle of a woman in obtaining her rights. Firdaus, the main character in Perempuan di Titik Nol, regards her struggle as a prostitute is more respected than has to become a wife of sheikh, who undergo oppression and physical abuse, and is used as an object of satisfying man desire that is worthless. By being a prostitute, she thinks that she has more freedom of her own body. Meanwhile, the main character in Midah Si Manis Bergigi Emas, Midah, regards her struggle of life as a prostitute as freedom in terms of gender equality because she can choose her own way of life without having to be managed by any man. Midah does not get more physical oppression as what Firdaus experiences, especially as a victim of physical abuse from her husband and other men.